La Caballa (Scomber scombrus L., 1758) del Atlántico nordeste: estudio biológico y de la población en aguas del norte y noroeste de la península Ibérica - Villamor, Begoña (2008)
The present thesis aims to gain a broader understanding of the biological characteristics of the Northeast Atlantic mackerel Scomber scombrus L., 1758 in the waters of the north and northwest of the Iberian Peninsula. The main aspects dealt with are: population structure; growth in the larval, juvenile and adult stages; and how oceanographic factors affect mackerel biology and recruitment processes. For the purposes of most of the aims of the study, data from both the fishing activity in waters of Galicia and the Cantabrian Sea and from fishing research surveys were used. First, the study area (north and northwest of the Iberian Peninsula) and the biological and fishing characteristics of the pelagic ecosystem in the study area are described. The Northeast Atlantic mackerel is also described, including the species' general characteristics (taxonomy, morphology, and biology), general spatial distribution, and fisheries. The mackerel migratory pattern is documented, as well, based on the analysis of the spatial and temporal distribution of the fishery and on the abundance of the species along the coasts north of Spain. The results of the tagging-recovery experiments carried out off the north and northwest Iberian Peninsula are then presented, together with the contribution they have made to our current state of knowledge regarding migrations made by mackerel in the Northeast Atlantic, and thus of stock's structure and assessment. The migratory patterns are shown to be parallel for all the Northeast Atlantic mackerel. The patterns of annual growth of mackerel juveniles and adults and their interannual variability are examined, the growth patterns from different areas compared, and the reasons underlying the temporal and geographical variability in mackerel growth and possible influences on the assessment and management of this stock are discussed. Moreover, the microstructure of otoliths from mackerel larvae and juveniles are analysed, and the different daily growth models are compared, in order to determine which ...